PENGARUH PEMBERIAN PUPUK HAYATI MIKORIZA DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG PANJANG (Vigna sinensis L.) DI ULTISOL - Eisal Vepin Nainggolan; Yudhi Harini Bertham; Sigit Sudjatmiko (BPFP Universitas Bengkulu, 2020)
[EFFECT OF MYCORRHIZAL BIOFERTILIZER AND CHICKEN MANURE ON GROWTH AND YIELD OF COWPEA (Vigna sinensis L.) IN ULTISOL]. This study aims to 1) obtain the interaction of mycorrhizal biofertilizers and chicken manure on cowpea in ultisol and 2) determine the best dose of mycorrhizal biofertilizers for the growth and yield of cowpea plants, also find the best dose of chicken manure on the growth and yield of string beans. The study was conducted in April 2019 at the experimental garden, Integrated Zone of the Faculty of Agriculture, UNIB, Kelurahan Kandang Limun, Muara Bangkahulu District, Bengkulu City. This study used a factorial Randomized Completely Block Design (RCBD) with two factors and three replications. The first factor is the administration of a dose of mycorrhizal biofertilizer, i.e., 0 (without mycorrhizae), 2.5 g/plant, 5 g/plant, and 7.5 g/plant. The second factor is the provision of chicken manure doses of 5 tons/ha, 10 tons/ha, and 15 tons/ha. Each experimental unit consisted of 25 plants with some sample plots of 5 plants. There is an interaction between mycorrhizal fertilizer 5 g / plant with chicken manure 5 tons/ha, which gives the best results on variable weight pod pods equal to 1.55 kg/m2 and pod weight of 15.46 kg/ha. The application of mycorrhizal biological fertilizer at a dose of 5 g/plant has good vegetative growth compared to other mycorrhizal doses. It shows the highest results based on the average number of flowers/plants and the number of pods/plants. Doses of chicken manure up to a dose of 15 tons/ha do not significantly increase growth and yield of cowpea.